What explains the socioeconomic status-health gradient? Evidence from workplace COVID-19 infections. (June 2022) - Godefroy, Raphael; Lewis, Joshua
Abstract: This paper studies the contribution of the workplace to the SES-health gradient. Our analysis is based on a unique dataset that tracks various health outcomes and workplace risks among healthcare workers during the first four months of the coronavirus 2019 (COVID-19) pandemic. The setting provides an exceptional opportunity to test for work-related disparities in health, while controlling for confounding determinants of the SES-health gradient. We find that low-SES nurses were systematically more likely to contract COVID-19 as a result of workplace exposure. These differentials existed in all healthcare institutions, but were particularly large in non-hospital settings. In contrast, we find no relationship between SES and nonwork-related infection rates. The differences in workplace infection rates are substantially larger than those implied by standard 'task-based' indices of transmission risk, and cannot be attributable to easily identifiable metrics of workplace risk. Together, our results show how subtle differences in work conditions or job duties can substantially contribute to the SES-health gradient. Highlights: The risks of workplace COVID-19 infection differed widely for workers in different healthcare occupations. Work-related COVID-19 infections were highest among lower status occupations. The differentials were present in all healthcare institutions, but largest in non-hospital settings. Standard 'task-based' indices of workplace transmission risk substantially underestimate the COVID-19 infection gradient.